A preliminary examination of shoulder joint function following shoulder complex training and in-season play in youth baseball players - Carlson, K. M.; Tweedt, K.; Strelecki, M.; Malaby, I.; Seymour, C. (International Journal of Kinesiology & Sports Science, 2020)
Background: As shoulder care continues to be a concern for youth baseball players, coaches, parents, researchers and clinicians, shoulder complex care should remain a point of emphasis especially for in overhead athletes. The impact of throwing volume and shoulder care is important for us to understand. Objective: The purpose was to examine the changes in shoulder complex function during a playing season combined with shoulder complex training in young male baseball players. Methods: Eleven male baseball players (11-15 y/o) served as subjects. Pre-testing included shoulder joint internal/external rotation peak torque and average work as measured with isokinetic dynamometry (Biodex System 4Pro). Training over the 18-week project duration was Crossover Symmetry "Activation" and "Strength" protocols completed per manufacturer recommendations. Adherence was tracked via a weekly email sent to the subject`s guardian to self-report completed training. Post-testing was conducted at the conclusion of the 18th week. Paired sample t-tests compared pre-test and post-test mean differences for peak torque and average power (p<0.05). Results: All-subject average for training was 54 sessions over the 18 weeks. Estimated number of throws completed during practice and games over the 18 weeks was 8,400. For both testing speeds and for both internal and external shoulder joint rotation, peak torque increases ranged from ~50% for external rotation at 60 deg/s up to ~200% for internal rotation at 120 deg/s. Statistical differences (p<0.001) were noted between all pre-test and post-test internal and external rotation peak torque values. For both testing speeds and for both internal and external shoulder joint rotation, average power increases ranged from ~38% at 60 deg/s for external rotation up to ~200% at 120 deg/s for internal rotation. Statistical differences (p<0.005) were noted between all pre-test and post-test internal and external rotation average power values. Conclusions: Substantial increases in shoulder joint rotation peak torques and power were seen across the 18-week study duration. As this was a preliminary investigation, we have yet to discern if these increases are due to the shoulder complex training or volume of throwing that was completed.